Deriving position of inverse bending roll by experiment and analysis (High precision roll bending of titanium alloy wire for glasses frame) - Yoshinori SASAKI; Masaaki OTSU; Masami MATSUMURA; Kazuyuki MORISHITA; Taiki TANAKA; Hideki YAGI; Yuichiro SEKINE; Motoo ASAKAWA (Nihon Kikai Gakkai ronbunshu, 2015)
In forming of glasses frame, bending and inverse bending of rim wires with 4 rolls are usually employed. Only an inverse bending roll, the 4th roll, can change the position to control the curvature of the rim wire. A deriving method of inverse bending roll position is proposed in this study. The proposed method requires not the computational simulations but only some simple steady inverse bending experiments to obtain a relationship between inverse bending roll position and bent curvature which depends on machine condition and bent wire. The experimentally obtained relationship is used in the formulation of deriving the inverse bending roll position. To validate the proposed method, a real glasses frame shape is formed by the proposed and conventional methods. The difference between the designed and formed shapes is evaluated by a sum of absolute shape deviation. The value by the proposed method is smaller up to about 75% than that by the conventional method.